CULTURAL ADAPTATION AND PSYCHOMETRIC VALIDATION OF THE SELF EFFICIENCY AND PERFORMANCE IN SELF-MANAGEMENT SUPPORT (SEPSS) QUESTIONNAIRE IN UNDERGRADUATE NURSING AND MEDICAL STUDENTS OF BANGLADESH - Mohammed Abdul Aziz , Masood (2023)
In an aging society, healthcare professionals and students face increasing demands to actively involve patients in the decision-making process regarding their health conditions and lifestyles. Self-management support is considered a best practice that aligns with the patient-centered care paradigm in Bangladesh. However, there is currently no instrument available to assess healthcare professionals’ competencies in this field, particularly during their early education and training period. The aim of this study was to translate the Self Efficiency and Performance in Self-management Support (SEPSS) instrument into Bangla and validate its psychometric properties in a sample of undergraduate healthcare students in Bangladeshi higher education institutions. A cross-sectional study was conducted to assess the reliability, validity, and cultural appropriateness of the Bangla version of SEPSS-36 among 486 nursing and medical students. Confirmatory factor analysis was carried out using the chi-square model fit index (CMIN), comparative fit index (CFI), and Root Mean Square Error of Approximation (RMSEA) as fit indices. The internal consistency was estimated by the Cronbach alpha coefficient. The results indicate that the CMIN (2.658) and RMSEA (.058) values suggest that the sample data and hypothetical model are an acceptable fit in the analysis, with satisfactory CFI values (.895). The reliability for all SEPSS dimensions was acceptable. The Bangla version of the SEPSS questionnaire is a valid and reliable instrument that can assist healthcare educators and researchers in determining students’ competencies within this domain.